Depression and suicide in adults with autism spectrum disorder: A systematic review (Research, Society and Development, 2022)
Objective: To identify predominance and risk factors for depression and suicidal ideation/attempts in adults with Autism Spectrum Disorder (ASD). Methods: This is a qualitative, systematic review of the prevalence and risk factors for depression and suicidal ideation/ attempts in adults with ASD. This study has made use of the virtual databases PubMed, LILACS, and SciELO over a period of five years, using keywords such as “autism”, “depression”, “adults” and “suicide” as describers to search for articles. Results: The fifteen articles addressed the high predominance of depression and suicidal ideation/attempts and their risk factors in adults with ASD. Conclusions: Autistic adults are at high risk of developing depression and suicidal ideation and attempts. They are exposed to several risk factors, many of them linked to their own specific characteristics. It is clear that studies on this subject are still in their early stages. Because of this, there are still no specific instruments for the assessment of depression and the risk of suicide in this group. Therefore, it is concluded that there is a need for longitudinal studies to better assess the predominance and risk factors for depression and suicidal ideation/attempts in adults with ASD. Thus, the goal is to develop specific and effective tools for screening and diagnosing these psychiatric pathologies, as well as to increase and improve risk factor delimitation. Consequently, strategies to prevent illnesses in this group could be designed with even more effectiveness.